The Influence of Financial Literacy, Self-Control, and Cashless Society on Consumptive Behavior of Faculty of Economics and Business Students at Universitas Cenderawasih - Mike Stevenson Tokoro; Nadia Safirah (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to determine the influence of Financial Literacy, Self-Control, and the Cashless Society, both partially and simultaneously. A quantitative method was employed, with data analysis conducted using the Statistical Package for the Social Sciences (SPSS) version 29 to examine the variables in this research. Data were collected through field studies and literature reviews. The sampling technique used was purposive sampling, with a total sample of 100 students. Primary data were obtained by distributing questionnaires via Google Forms to students of the Management Department, while secondary data such as archives, documents, records, photographs, and similar sources were collected by the researcher. The data analysis applied quantitative techniques, including descriptive statistics, validity and reliability tests, normality tests, classical assumption tests, multiple regression analysis, F-tests, t-tests, and the coefficient of determination. The results show that, partially, Financial Literacy and Self-Control have a positive and significant effect on Consumptive Behaviour, whereas the Cashless Society variable does not have a significant effect. Simultaneously, Financial Literacy, Self-Control, and the Cashless Society have a significant effect on Consumptive Behaviour.